PROSES KREATIF RAJA AISYAH SULAIMAN, SASTRAWAN PEREMPUAN FEMINIS MELAYU ZAMAN PERALIHAN - Anggraeni, Nureza Dwi; Wiyatmi, Wiyatmi (Diksi, 2018)
Abstract                (Title: Creative Process of  Raja Aisyah Sulaiman, Feminist  Women's Literature in Melayu Transision Era). Raja Aisyah bint Raja Sulaiman Ibni Ali Haji or better known as Ayesha Sulaiman was one of the female writers in the Malay literary tradition of the Transitional period. As one of the literary grandchildren of Raja Ali Haji, his life is surrounded by a tradition of good literature. However, his name is unknown in the history of Malay literature. By using the perspective of ginikririk feminist literature, this study examines the creative process of Ayesha Sulaiman, especially in writing one of his works entitled Syair Khadamuddin. The results showed that Syair Khadamuddin was written Aisha Sulaiman to describe his life as a woman in Riau Lingga Malay Kingdom to continue with the sad story of a wife who experienced an inner struggle because of her attitude and outlook on single loyalty to her husband, longing for the abandoned homeland and views on family life and nationhood. The presence of Aisha Sulaiman's work in the transitional period from the 19th century to the 20th century, became a sign of a rebellion against patriarchal domination in Indonesia's local literary history which bound women.Keywords: feminist writers, Malay literature, transitions, ginokritik, poetry